Effects of high temperature and CO2 on intracellular DMSP in the cold-water coral Lophelia pertusa - Burdett, Heidi; Carruthers, Madeleine; Donohue, Penelope; Wicks, Laura; Hennige, Sebastian; Roberts, Murray; Kamenos, Nicholas (Marine Biology, 2015)
This paper is a contribution to the UK Ocean acidification research Programme (Natural Environment Research Council (NERC) grant NE/H017305/) and to the Marine Alliance for Science and Technology Scotland (MASTS). This research was conducted whilst HLB was initially in receipt of NERC studentship funding (NE/H525303/1) and ultimately a MASTS Research Fellowship, PJCD was in receipt of a MASTS PhD studentship, NAK was in receipt of Royal Society of Edinburgh/Scottish Government Fellow ship (RES 48704/1) and SJH was in receipt of a NERC Independent Research Fellowship (NE/K009028/1). SJH, LCW and JMR acknowledge support from Heriot–Watt University’s Environment and Climate Change Theme. Significant warming and acidification of the oceans is projected to occur by the end of the century. CO2 vents, areas of upwelling and downwelling, and potential leaks from carbon capture and storage facilities may also cause localised environmental changes, enhancing or depressing the effect of global climate change. Cold-water coral ecosystems are threatened by future changes in carbonate chemistry, yet our knowledge of the response of these corals to high temperature and high CO2 conditions is limited. Dimethylsulphoniopropionate (DMSP), and its breakdown product dimethylsulphide (DMS), are putative antioxidants that may be accumulated by invertebrates via their food or symbionts, although recent research suggests that some invertebrates may also be able to synthesise DMSP. This study provides the first information on the impact of high temperature (12°C) and high CO2 (817 ppm) on intracellular DMSP in the cold-water coral Lophelia pertusa from the Mingulay Reef Complex, Scotland (56°49′N, 07°23′W), where in situ environmental conditions are meditated by tidally induced downwellings. An increase in intracellular DMSP under high CO2 conditions was observed, whilst water column particulate DMS + DMSP was reduced. In both high temperature treatments, intracellular DMSP was similar to the control treatment, whilst dissolved DMSP + ...